2006
DOI: 10.1007/bf02913076
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of plasma homocysteine with lipid profile parameters in ischemic heart disease

Abstract: The present study was undertaken to explore the relationship of plasma homocysteine with other biochemical parameters in ischemic heart disease. Plasma levels of total homocysteine was measured by HPLC -fluorescence detection with internal standard in 60 ischemic heart disease patients and were compared with 30 age matched normal healthy controls. The significant increase of plasma homocysteine was observed in both myocardial infarction and chronic stable ischemic heart disease patients when compared with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 12 publications
2
19
0
Order By: Relevance
“…We have therefore concluded that there was no correlation between the hyperhomocysteinemia and the lipids. Our study is in agreement with those of De-Luis et al, [20] and Yadav et al, [21] who also had found no correlative link between the lipids and the hyperhomocysteinemia. Corroborating our study, Momin et al, [7] also have found that the total and…”
Section: Open Access Http://scidocorg/ijdvrphp Discussionsupporting
confidence: 83%
“…We have therefore concluded that there was no correlation between the hyperhomocysteinemia and the lipids. Our study is in agreement with those of De-Luis et al, [20] and Yadav et al, [21] who also had found no correlative link between the lipids and the hyperhomocysteinemia. Corroborating our study, Momin et al, [7] also have found that the total and…”
Section: Open Access Http://scidocorg/ijdvrphp Discussionsupporting
confidence: 83%
“…In fact, increasing synthesis of Hcy may have an effect on the progression of atherogenesis [23,24]. Yadav et al, however, did not find a significant correlation between plasma Hcy and total cholesterol, HDL cholesterol or triglycerides [25]. Holven et al suggested that hyperhomocysteinaemic individuals have dysfunctional HDL particles with attenuated antiatherogenic activity and that this may represent a novel explanation for the increased risk of cardiovascular events in these individuals [26].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies in lipid profile analysis conducted on acute myocardial infarction patients (Mishra et al, 2001;Das et al, 2002;Goswami et al, 2003;Kharb et al, 2003;Malhotra et al, 2003;Burman et al, 2004;Rajashekhar et al, 2004;Sivaraman et al, 2004;Rani et al, 2005;Shindhe, et al, 2005;Yadhav et al, 2006;Patil et al, 2007) observed higher total cholesterol, triglyceride, low-density lipoprotein -cholesterol and lower levels of high-density lipoprotein-cholesterol in patients compared to controls.…”
Section: Observations Of Lipid Profilementioning
confidence: 99%